A study to assess the effect of pretreatment with intravenous palonosetron in preventing pain on propofol injection - Nethra Surhonne; Chaithali Hebri; Sudeesh Kannan (Journal of Medical Science, 2023)
Background. Propofol is widely used for induction, maintenance of anaesthesia and possess many characteristics of an ideal intravenous anaesthetic agent. It is known to cause severe, sharp, stinging or burning pain on injection which is considered to be unacceptable as it can cause agitation and interfere with smooth induction of anaesthesia. In this study we are comparing Palonosetron and Normal Saline in decreasing pain on injection of propofol during intravenous induction of anaesthesia.